Montelukast protects against renal ischemia/reperfusion injury in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2006)
Background: Oxygen free radicals are important components involved in the pathophysiological processes observed during ischemia/reperfusion (I/R). Objective: This study was designed to assess the possible protective effect of montelukast, a selective antagonist of cysteinyl leukotriene receptor 1 (CysLT1), on renal VR injury. Methods: Wistar albino rats were unilaterally nephrectomized and subjected to 45 min of renal pedicle occlusion followed by 6 h of reperfusion. Montelukast (10 mg kg(-1), i.p.) or saline was administered at 15 min prior to ischemia and immediately before the reperfusion period. At the end of the reperfusion period, following decapitation, kidney samples were taken for histological examination or for determination of renal malondialdehyde (MDA), an end product of lipid peroxidation; glutathione (GSH), a key antioxidant; and myeloperoxidase (MPO) activity, an index of tissue neutrophil infiltration. Formation of reactive oxygen species in renal tissue samples was monitored by using chemiluminescence (CL) technique with luminol and lucigenin probes. Creatinine, blood urea nitrogen and lactate dehydrogenase (LDH) activity were measured in the serum samples, while leukotriene B-4, TNF-alpha, IL-beta, JL-6 and total antioxidant capacity (AOC) were assayed in plasma samples. Results: Ischemia/reperfusion caused a significant decrease in renal GSH and plasma AOC, which was accompanied with significant increases in MDA level, MPO activity, and CL levels of the renal tissue concomitant with increased levels of the pro-inflammatory mediators, LDH activity, creatinine and BUN. On the other hand, montelukast treatment reversed all these biochemical indices as well as histopathological alterations induced by I/R. Conclusions: CysLT I receptor antagonist montelukast reversed I/R-induced oxidant responses, improved microscopic damage and renal function. It seems likely that montelukast protects kidney tissue by inhibiting neutrophil infiltration, balancing oxidant-antioxidant status, and regulating the generation of inflammatory mediators. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: leukotrienes; montelukast; ischemia/reperfusion; kidney; myeloperoxidase; cytokines; ISCHEMIA-REPERFUSION INJURY; SUPERIOR MESENTERIC-ARTERY; BLT RECEPTOR ANTAGONIST; LEUKOTRIENES; DYSFUNCTION; ETHANOL; SEPSIS; MICE